210Po/210Pb Disequilibria in the Eastern Tropical North Pacific - Ma, Qiang; Qiu, Yusheng; Zhang, Run; Lv, E; Huang, Yipu; Chen, Min (Frontiers in Marine Science, 2021)
The 210Po/210Pb disequilibrium was attempted to reveal the small-scale particle dynamics in the eastern tropical North Pacific. Seawater samples in the full water column were collected from three sites in the Tehuantepec bowl near the East Pacific Ridge for determination of dissolved and particulate 210Po and 210Pb. Our results show that TPo/TPb activity ratios in the full water column at the three sites are less than 1, with an average of 0.56, indicating that the total 210Po in the oligotrophic sea is significantly deficient. The activity ratios of DPo/DPb in the dissolved phase are less than 1, while those in the particulate phase are greater than 1 (except for the bottom 300 m), indicating fractionation between 210Po and 210Pb in the scavenging process. A negative linear relationship between 210Po deficit and silicate proves that biological activities are responsible for 210Po deficiency in the upper 200 m. However, the deficit of 210Po in the bottom 300 m may be caused by the horizontal transport of the hydrothermal plume. After correcting the horizontal contribution, the removal rates of 210Po for the 200–1,500 m and the bottom 300 m layers increased by 7.5–21 and 26.1–29.5%, respectively. Correspondingly, the variation range of the residence time of a total 210Po became smaller. Our calculations suggest that horizontal transport is acting as a stabilizer for small-scale variation in the 210Po deficit in the eastern tropical North Pacific. Our study highlights the need to pay more attention to the small-scale variation of 210Po deficit when applying 210Po/210Pb disequilibria to trace biogeochemical processes, and the mechanism responsible for this variation deserves further study.